2019
DOI: 10.5539/ijms.v11n4p77
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Analysis of Perceived Transaction Convenience, Performance Expectancy, Effort Expectancy and Behavior Intention to Mobile Payment of Cambodian Users

Abstract: Mobile payment (m-payment) is determined as modern application of electronic commerce. It helps financial institutions to widen the financial services to existing customers in developed countries and to increase financial inclusion in developing and emerging countries. Cambodia is a country with low financial inclusion and National Bank of Cambodia perceives that the usage of m-payment can help to increase financial deepness. However, the lack of empirical evidences is a concern and this study is developed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
2
3
1
1
Order By: Relevance
“…The higher the perception of ease of management of the Dana E-Wallet, the greater the probability of Behavioral Intention in its usage. This finding is consistent with previous research conducted by Hung et al (2019), Muangmee et al (2021), andSubawa andMimaki (2019), which concluded that Performance Expectancy has a positive and significant influence on Behavioral Intention. Noteworthy is the specific element within Performance Expectancy, the perception of ease of management, which bears substantial influence on Behavioral Intention in employing the Dana E-Wallet.…”
Section: The Influence Of Performance Expectancy On Behavioral Intentionsupporting
confidence: 93%
See 1 more Smart Citation
“…The higher the perception of ease of management of the Dana E-Wallet, the greater the probability of Behavioral Intention in its usage. This finding is consistent with previous research conducted by Hung et al (2019), Muangmee et al (2021), andSubawa andMimaki (2019), which concluded that Performance Expectancy has a positive and significant influence on Behavioral Intention. Noteworthy is the specific element within Performance Expectancy, the perception of ease of management, which bears substantial influence on Behavioral Intention in employing the Dana E-Wallet.…”
Section: The Influence Of Performance Expectancy On Behavioral Intentionsupporting
confidence: 93%
“…Considering the utility, motivation, and benefits derived from using information technology, users develop an interest in utilizing technology to enhance their performance. Performance Expectancy consistently and significantly influences the intention to use information technology (Hung et al, 2019;Muangmee et al, 2021;Subawa & Mimaki, 2019). One specific item within Performance Expectancy, namely the perception of ease of management, has a significant impact on Behavioral Intention in using the Dana E-Wallet.…”
Section: The Influence Of Performance Expectancy On Behavioral Intentionmentioning
confidence: 99%
“…Convenience has been discussed as an important factor in influencing technology adoption because convenience means that users believe that a new technology or system is able to help them complete their tasks and fulfil what they want (Chawla dan Joshi, 2018). In the use of mobile banking, transaction convenience is defined as the ease with which users can perform and modify transactions (Hung et al, 2019). The convenience provided in service is able to moderate the relationship between the dimensions of service quality (outcome, interaction, and environment) and the overall quality of mobile banking services.…”
Section: Mobile and Internetmentioning
confidence: 99%
“…Lebih lanjut, studi terdahulu menjelaskan bahwa performance expectancy memiliki pengaruh positif terhadap niat perilaku dalam menggunakan sistem pembayaran mobile pada studi yang dilakukan di Iran terhadap pengguna e-banking (Hung et al, 2019). Telah dibuktikan pula pada studi yang dilakukan di negara Taiwan bahwa performance expectancy merupakan prediktor utama yang menentukan niat perilaku dalam menggunakan web layanan digital (Yu et al, 2021).…”
Section: Performance Expectancy Terhadap Attitude Dan Behavioral Inte...unclassified